Detection of Quorum Sensing Signal Molecules, Particularly N-Acyl Homoserine Lactones, 2-Alky-4-Quinolones, and Diketopiperazines, in Gram-Negative Bacteria Isolated From Insect Vector of Leishmaniasis - Vivero-Gomez, Rafael Jose; Mesa, Gustavo Bedoya; Higuita-Castro, Jorge; Robledo, Sara M.; Moreno-Herrera, Claudia X.; Cadavid-Restrepo, Gloria (Frontiers in Tropical Diseases, 2021)
Gram-negative bacteria are known to use a quorum sensing system to facilitate and stimulate cell to cell communication, mediated via regulation of specific genes. This system is further involved in the modulation of cell density and metabolic and physiological processes that putatively either affect the survival of insect vectors or the establishment of pathogens transmitted by them. The process of quorum sensing generally involves N-acyl homoserine lactones and 2-alkyl-4-quinolones signaling molecules. The present study aimed to detect and identify quorum sensing signaling molecules of AHLs and AHQs type that are secreted by intestinal bacteria, and link their production to their extracellular milieu and intracellular content. Isolates for assessment were obtained from the intestinal tract of Pintomyia evansi (Leishmania insect vector). AHLs and AHQs molecules were detected using chromatography (TLC) assays, with the aid of specific and sensitive biosensors. For identity confirmation, ultra-high-performance liquid chromatography coupled with mass spectrometry was used. TLC assays detected quorum sensing molecules (QSM) in the supernatant of the bacterial isolates and intracellular content. Interestingly, Pseudomonas otitidis, Enterobacter aerogenes, Enterobacter cloacae, and Pantoea ananatis isolates showed a migration pattern similar to the synthetic molecule 3-oxo-C6-HSL (OHHL), which was used as a control. Enterobacter cancerogenus secreted C6-HSL, a related molecules to N-hexanoyl homoserine lactone (HHL), while Acinetobacter gyllenbergii exhibited a migration pattern similar to 2-heptyl-4-quinolone (HHQ) molecules. In comparison to this, 3-oxo-C12-HSL (OdDHL) type molecules were produced by Lysobacter soli, Pseudomonas putida, A. gyllenbergii, Acinetobacter calcoaceticus, and Pseudomonas aeruginosa, while Enterobacter cloacae produced molecules similar to 2-heptyl-3-hydroxy-4-quinolone (PQS). For Pseudomonas putida, Enterobacter aerogenes, P. ananatis, and Pseudomonas otitidis extracts, peak chromatograms with distinct retention times and areas, consistent with the molecules described in case of TLC, were obtained using HPLC. Importantly, P. ananatis produced a greater variety of high QSM concentration, and thus served as a reference for confirmation and identification by UHPLC-MRM-MS/MS. The molecules that were identified included N-hexanoyl-L-homoserine lactone [HHL, C10H18NO3, (M + H)], N-(3-oxohexanoyl)-L-homoserine lactone [OHHL, C10H16NO4, (M + H)], N-(3-oxododecanoyl)-L-homoserine lactone [OdDHL, C16H28NO4, (M + H)], and 2-heptyl-3-hydroxy-4(1H)-quinolone [PQS, C16H22NO2, (M + H)]. Besides this, the detection of diketopiperazines, namely L-Pro-L-Tyr and ΔAla-L-Val cyclopeptides was reported for P. ananatis. These molecules might be potentially associated with the regulation of QSM system, and might represent another small molecule-mediated bacterial sensing system. This study presents the first report regarding the detection and identification of QSM and diketopiperazines in the gut sand fly bacteria. The possible effect of QSM on the establishment of Leishmania must be explored to determine its role in the modulation of intestinal microbiome and the life cycle of Pi. evansi.